Comparison of the Effectiveness of Individual and Group Psychodrama on Life Satisfaction, Self-Compassion, and Positive Emotions in Depressed Patients - Bagherian, Mandana; Azadi, Mehran; Azad Abdullahpour, Mohammad (International Journal of Education and Cognitive Sciences, 2022)
Purpose: This study aimed to compare the effectiveness of individual and group psychodrama on life satisfaction, self-compassion, and positive emotions in depressed patients. Methods and Materials: This quasi-experimental study employed a pretest-posttest with a control group design. The sample consisted of 45 women aged 25 to 45 years, diagnosed with depression based on the Beck Depression Inventory (BDI). Participants were randomly assigned to three groups: individual psychodrama (n = 15), group psychodrama (n = 15), and control (n = 15). The psychodrama interventions were conducted over 12 weekly sessions, each lasting 90 minutes. The Satisfaction with Life Scale (SWLS), the Self-Compassion Scale (SCS), and the Positive and Negative Affect Schedule (PANAS) were administered before and after the intervention, with a follow-up assessment after three months. One-way repeated measures ANOVA, followed by Bonferroni and Tukey post-hoc tests, were conducted to analyze within-group and between-group differences. Findings: The results showed that both individual and group psychodrama significantly improved life satisfaction, self-compassion, and positive emotions compared to the control group (p < .001). Post-hoc analyses revealed that the increase in scores from pretest to posttest was statistically significant in both psychodrama groups (p < .05), with no significant difference between the two modalities (p > .05). The follow-up assessments indicated that these improvements remained stable over time. Conclusion: These findings suggest that psychodrama, whether delivered individually or in a group format, is an effective intervention for improving life satisfaction, self-compassion, and positive emotions in depressed patients.